Analisis Efektifitas Para Pesepeda di Kecamatan Garut Kota - Ida Farida; Riska Amalia Nasrillah (Jurnal Konstruksi, 2024)
This research is intended as input in formulating policies for building bicycle lanes to support cyclists who do not have special lanes when on the road, most people cycle around the Garut City Square. Data collection in bicycle lane planning includes bicycle use preference surveys, geometric surveys, counting, interviews and road equipment. In the data analysis technique, the characteristics of the respondents and the bicycle lane design were obtained. From the results of the analysis of bicycle lane planning using several data analysis methods which are used to determine the need for bicycle lanes that meet the criteria and theory of bicycle lane planning itself. The optimum route is obtained based on the number of people cycling, the width of the road, and obstacles in the form of haphazard parking. The results of this research are a bicycle lane design with the bike lane concept, namely where the bicycle lane is on the road, differentiated by paint or road markings. The width of the bicycle lane created is 1 meter, enough for one bicycle user to be right on the route with the route from Garut Square ”“ Jl. Pramuka ”“ Jl. Banks ”“ Jl. Veterans ”“ Jl. Ahmad Yani.